2018
DOI: 10.1093/cid/ciy1047
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired Respiratory Viruses Are a Risk Factor for Chronic Lung Allograft Dysfunction

Abstract: Background The relationship between community-acquired respiratory viruses (CARVs) and chronic lung allograft dysfunction (CLAD) in lung transplant recipients is still controversial. Methods We performed a prospective cohort study (2009–2014) in all consecutive adult patients (≥18 years) undergoing lung transplantation in the Hospital Universitari Vall d’Hebron (Barcelona, Spain). We systematically collected nasopharyngeal sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 42 publications
6
55
1
Order By: Relevance
“…Both prospective 21,44,45 and retrospective studies 46 support a link between CARVs and chronic rejection, particularly when the infection involves the lower respiratory tract and/or is associated with clinical symptoms. 46,47 anti-donor HLA antibodies, 39,40 as well as ColV and Kα1T autoantibodies as risk factors for CLAD. 8,48 Similarly, we did not find a correlation between donor-specific alloreactive T cells responsiveness (as assessed by cytokine ELISPOT) in contrast to studies in kidney transplant recipients where ELISPOT reactivity strongly correlates with long-term renal graft function.…”
Section: Discussionmentioning
confidence: 99%
“…Both prospective 21,44,45 and retrospective studies 46 support a link between CARVs and chronic rejection, particularly when the infection involves the lower respiratory tract and/or is associated with clinical symptoms. 46,47 anti-donor HLA antibodies, 39,40 as well as ColV and Kα1T autoantibodies as risk factors for CLAD. 8,48 Similarly, we did not find a correlation between donor-specific alloreactive T cells responsiveness (as assessed by cytokine ELISPOT) in contrast to studies in kidney transplant recipients where ELISPOT reactivity strongly correlates with long-term renal graft function.…”
Section: Discussionmentioning
confidence: 99%
“…Among a total of 1,007 patients, sole HMPV infection was identified in 57 cases, of which 35% were associated with acute rejection within 3 months, followed by CLAD/BOS (151). However, in other studies, reactivation of cytomegalovirus has been identified as an important cofactor that is not exclusive to HMPV (61).…”
Section: Human Pneumo-and Paramyxoviridaementioning
confidence: 97%
“…In a prospective cohort study from 2009 to 2014 enrolling 98 lung transplant recipients, CLAD was diagnosed in 38% at a median time of 20.4 months (IQR, 12 to 30.4) (61). In the time-controlled multivariate analysis, CLAD was associated with CARV-LRTID (HR, 3.00; 95% CI, 1.52 to 5.91; P ϭ 0.002), acute rejection (HR, 2.97; 95% CI, 1.51 to 5.83; P ϭ 0.002), and CMV pneumonitis (HR, 3.76; 95% CI, 1.23 to 11.49; P ϭ 0.02) (61).…”
Section: General Aspects Of Carvs In the Transplant Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have previously reported, permanent discontinuation of the antimetabolite in KT patients with a severe viral infection such as CMV and BK virus is safe and effective [ 76 , 77 ]. However, there are less data about the safety of the prolonged cessation of antimetabolites in other organ transplants, particularly for viruses in whom the disease severity is characterized by a hyperactive immune response, or for conditions such as in thoracic transplant where respiratory viral infections have been shown to trigger immune responses that induce chronic allograft dysfunction [ 78 81 ].…”
Section: Outpatient Management For Transplant Recipientsmentioning
confidence: 99%